English Channel Glycymeris glycymeris increment widths - Holmes, Sarah; Butler, Paul; Scourse, James; Richardson, Christopher; Halloran, Paul; Catherall, Claire (PANGAEA, 2025)
Live specimens and dead shell valves of the dog cockle (Glycymeris glycymeris) were collected from the seabed using a dredge in September 2013. The collection site was Mid-South Cornwall (49° 50.821'N, 03° 11.93'W) at depths of 70-71 m. A total of 29 shells were collected, of which four were live specimens used to anchor the chronology in time. After obtaining the increment-width measurements from each shell, the age-related trend was removed by fitting a negative exponential curve to the power-transformed data and the resulting record was prewhitened retaining environmental correlation using the software ARSTAN.
Keywords: Bivalve; bivalves growth; English Channel; Glycymeris; sclerochronology